Fauna and ecology of Spirurida in cattle of Uzbekistan - F. D. Akramova; D. A. Azimov; U. A. Shakarbaev; A. U. Mirzaeva; M. E. Gaipova; K. A. Saparov (Российский паразитологический журнал, 2019)
Objective of research: The objective of this study was to investigate the fauna, features of distribution and ecology of nematodes of the order Spirurida - parasites of cattle from Uzbekistan. Material and methods. Cattle and isolated animal organs were investigated by the method of complete and incomplete autopsies. Blood samples and animal skin biopsies were studied. Flies (Diptera) and beetles, intermediate hosts of nematodes, were collected and studied in places of cattle concentration, in spring, summer and autumn. Results and discussion: In animals of Uzbekistan 11 species of Spirurida nematodes belonging to two suborders were identified. Spirurata are represented by 7 species, Filariata by 4. The landscape distribution of the mentioned species of Spirurida and their biocenotic connections to corresponding hosts under conditions of Uzbekistan were determined.